ANALYSIS OF SOCIO - DEMOGRAPHIC FACTORS IN INCREASING RECIDIVISM IN PEMATANG SIANTAR CLASS IIA PRISON - Purba, Lydia Togu Swastika; Jarodi, Odi (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study analyzes the socio-demographic factors that influence the increase in recidivism at Pematang Siantar Class IIA Correctional Facility. Data shows an increase in the number of recidivist prisoners each year, with factors such as age, gender, education, and social environment playing an important role in the tendency of former prisoners to re-offend. This study uses qualitative methods through interviews and observations to identify the relationship between these socio-demographic factors. The results show that prisoners who are younger, male, lower education, and less supportive social environment are more vulnerable to becoming recidivists. This study recommends a rehabilitation program that focuses more on skill building, psychosocial support, and family and community involvement in supporting the reintegration of ex-prisoners. Keywords: Recidivism; Socio-Demographics; Prisons; Rehabilitation; Reintegration